2012
DOI: 10.5539/jfr.v1n3p84
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Organoleptic Properties of Wheat (Triticum aestivum) and Beniseed (Sesame indicum) Composite Flour Baked Foods

Abstract: Eating snacks during lunch periods has become a way of life for school children and the busy working class people in most urban cities in developing nations like Nigeria. Providing nutritious and healthy snacks remains a major challenge for the food industry to tackle, including the issue of sugar and carbohydrate contents in snacks which predisposes obesity. Nutritional and sensory characteristics of baked foods produced from wheat/beniseed flour composite were investigated with the aim of producing healthy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
3
8
0
Order By: Relevance
“…There was a slight increase in the moisture content of bread prepared from wheat-pigeon pea composite flour. The increase in moisture content could be because of increasing protein level from increasing pigeon pea flour addition [11], also, another author confirmed that grain's protein attracts moisture [3]. Moisture contents in the biscuits samples were low.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There was a slight increase in the moisture content of bread prepared from wheat-pigeon pea composite flour. The increase in moisture content could be because of increasing protein level from increasing pigeon pea flour addition [11], also, another author confirmed that grain's protein attracts moisture [3]. Moisture contents in the biscuits samples were low.…”
Section: Resultsmentioning
confidence: 99%
“…In its totality, 100 g of mature raw pigeon peas provides 114% of the daily requirement of folate. The levels of saturated fat, cholesterol, and sodium in Pigeon pea are low [3]. Therefore, pigeon pea, like other legumes is a healthy substitute for meats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The looming economic need by African countries in harnessing the high carbohydrate qualities of their indigenous root and tuber crops has facilitated their use in conjunction with wheat in several composite flours which have been utilized in an array of food products (Himeda et al 2014;Chandra et al 2015). Replete studies have investigated the utilization of both Trifoliate yam and beniseed flours as part of composite flour blends with cassava and wheat flour or both in the production of snacks, confectionaries, pastries and bread which provided remarkable outcomes (Abiodun et al 2010;Ezeocha et al 2011;Eke-Ejiofo and Owuno, 2012;Emmanuel-Ikpeme et al 2012). However, there has not been any reported investigation of the utilisation of composite flour mix of wheat, beniseed and trifoliate yam.…”
Section: Introductionmentioning
confidence: 99%
“…It is limiting in sulphur amino acids as is usual in vegetable origin proteins. When compared with other root crops, it has the highest content of phosphorus (P), magnesium (Mg) and Zinc (Zn) [1]. Taro starch contains about 50 % less amylose and an amylopectin content which is higher compared to other cereals.…”
Section: Introductionmentioning
confidence: 99%